On estimates of approximation characteristics of the Besov classes of periodic functions of many variables - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We obtain order estimates for some approximate characteristics of the Besov classes B p,ϑ r of periodic functions of many variables.